Road to the restoration of the Ohrid Archbishopric - Borisov Dejan, Борисов Дејан (Православен богословски факултет „Свети Климент Охридски“ - Скопје, 2017)
The restoration of the abolished Ohrid Archbishopric did not begin with the process at end of the World War II, but immediately after its abolition in the eighteen century. The restoration of the Ohrid Archbishopric as the Macedonian Orthodox Church is in full accordance with the Church tradition and practices established by the other Local Orthodox churches in the process of obtaining their autocephaly during the nineteenth adn twentieth centuries.
Јубилеен зборник по повод 50-годишнината од прогласувањето на автокефалноста на Македонската православна црква - Охридска архиепископија OCCASIONAL PAPERS ON THE RELIGION IN EASTERN EUROPE, Special Issue for the Fiftieth Anniversary of the Declaration of the Autocephaly of the Macedonian Orthodox Church
Keywords: Ohrid Archbishopric, Metropolitan Theodosius (Gologanov), Bulgarian Exarchate, Constantinople Patriarchate, Autocephalous United Orthodox Church of the Kingdom of Serbs, Croats and Slovens, autocephaly